SEDATION ASSESSMENT IN MECHANICAL VENTILATED PATIENTS: THE LEVEL OF KNOWLEDGE ASSESSMENT AMONG CRITICAL NURSES IN A PUBLIC TERTIARY CARE HOSPITAL LAHORE - RAIZ , G; BRUCE , S; AMIR , Z; TASNEEM , SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
By appropriately evaluating and controlling sedation in patients on mechanical ventilation, nursing problems can be prevented. However, critical care nurses in public tertiary care hospitals with limited training and resources continue to lack certain expertise. Critical care nurses need to assess and manage sedation. Patients are at significant risk from both over and insufficient sedation. Critical care nurses must possess adequate expertise in sedation assessment and management. Objective: The study's objective is to evaluate critical care nurses' knowledge in sedation management for patients on mechanical ventilation at Pakistan's public tertiary care hospitals. Method: A cross-sectional study with a descriptive design was carried out at the public tertiary care hospital in Lahore. Convenience sampling techniques were used to recruit study participants from the critical care unit. Knowledge levels were divided into three categories: poor, fair and good. Data was collected through questionnaires, which were evaluated using descriptive statistical analysis. Results: The result showed that 36% had fair knowledge, just 16% of the nurses had a strong understanding of sedation management, and 48% of the nurses had low knowledge. Conclusion: The study highlighted a significant lack of sedation management knowledge among critical care nurses in public tertiary care hospitals. Addressing these gaps through targeted training and standardized sedation protocols is essential for improving patient safety in critical settings.